Relavansi Konsep Akhlak Penghafal Al Qur’an Terhadap Perkembangan Kompetensi Afektif Santri di Unit KMT Darusy Syahadah Boyolali - Saubari Abdullah, Muhammad (Risâlah Jurnal Pendidikan dan Studi Islam, 2026)
The purpose of this research is to analyze the relevance of the concept of moral conduct among memorizers of the Qur'an as described in the book "Hilyatu Ahlil Qur'an" to the development of affective competencies among Qur'an memorization students. This study provides benefits by enriching the scholarly knowledge base of Islamic religious education and aiding in a deeper understanding of the concept of moral conduct among Qur'an memorizers, particularly for researchers, educational practitioners, and as a reference for educational institutions.This research is qualitative in nature, employing a descriptive qualitative approach to describe the concept of moral conduct among Qur'an memorizers derived from the book "Hilyatu Ahlil Qur'an" compiled by the Research and Information Center for Qur'anic Studies of Imam Asy Syathiby Institute. It also seeks to ascertain its relevance to the affective competencies of students. This thesis utilizes field research methodology, involving direct observation through field observations, interview tests, and questionnaire distribution. Data collection techniques include triangulation, which combines various data collection techniques and data sources through participant observation, in-depth interviews, and documentation. Thefindings of this research elucidate the concept of moral conduct for Qur'an memorizers, the pattern of moral development among students, and its relevance to the development of affective competencies among Qur'an memorization students. Concepts identified include moral conduct towards oneself, towards teachers, towards peers, towards the mosque, and towards academic life. The relevance of applying these concepts in various activities within the Islamic boarding school context demonstrates a positive development in the overall affective competencies of students and a strong correlation between the applied moral conduct concepts and the development of affective competencies across various domains.